An electrochemical sensing platform of cobalt oxide@gold nanocubes interleaved reduced graphene oxide for the selective determination of hydrazine - Shahid, Muhammad Mehmood; Rameshkumar, Perumal; Basirun, Wan Jefrey; Wijayantha, Upul; Chiu, Wee Siong; Khiew, Poi Sim; Huang, Nay Ming (Elsevier, 2018)
Reduced graphene oxide-cobalt oxide nanocube@gold (rGO-Co3O4@Au) nanocomposite was prepared using a one-pot hydrothermal synthesis. The nanocomposite was characterized using the UV-Vis absorption spectroscopy, field emission scanning electron microscopy (FESEM), high resolution transmission electron microscopy (HRTEM), energy dispersive X-ray (EDX) mapping, X-ray diffraction (XRD) and Raman analyses. The EDX mapping analysis showed the uniform distribution of Au nanoparticles on the Co3O4 surface that made the surface more roughness. The higher degree of reduction of GO was confirmed from the increased intensity ratio of the D and G bands (ID/IG) of the Raman spectrum during the hydrothermal synthesis. The rGO-Co3O4@Au nanocomposite exhibited good electrocatalytic activity towards the oxidation of hydrazine in phosphate buffer (pH 7.2). The detection of hydrazine was carried out using amperometry technique and the current response was linear in the range of 10–620 μM. The limit of detection was found to be 0.443 μM. The selectivity of the nanocomposite for the sensing of hydrazine was studied with the interferents such as NO3 −, SO4 2−, Cl−, Ag+, Na+, K+, ethanol, 4-nitrophenol, ascorbic acid and glucose. The sensing of different concentration of hydrazine present in the real water samples was analysed and an appreciable recovery was found.